An Introduction to Literary Quaranic Stylistics - Almenoar, Lubna (Journal of the American Academy of Special Education Professionals, 2010)
A stylistic analysis is one approach of analyzing a literary text using literary descriptions. The use of literary texts in the literature classroom has been limited to mostly Western sources. This paper is an attempt to create an awareness of the linguistic features present in the English language translations of the meaning of the Quran. The Surah (chapters of the Quran) in the English translated versions of the Quran prove to contain a rich variety of linguistic features. Using the English language translations of the meaning of the Quran as literary texts for the teaching of literature in the English language, especially at Islamic institutions, and using the stylistics approach to analyze these texts in the Literature classroom is a new and creative contribution towards the pedagogy of English language teaching. This paper also seeks to discuss the aims of stylistics in relation to the study and the teaching of literature. Besides reading literature, one can gain considerable pleasure from analyzing literature. One enjoys reading literature because it is interesting, enjoyable and/or emotionally touching. This enjoyment can be brought about by reading. Although reading is an important step in the study of the literary texts, there is another more important step–to analyze the literary texts, which is, to struggle to explain how one comes to understand literary works.